Fructans As DAMPs or MAMPs: Evolutionary Prospects, Cross-Tolerance, and Multistress Resistance Potential - Versluys, Maxime; Tarkowski, Łukasz P.; Van den Ende, Wim (Frontiers in Plant Science, 2017)
This perspective paper proposes that endogenous apoplastic fructans in fructan accumulating plants, released after stress-mediated cellular leakage, or increased by exogenous application, can act as damage-associated molecular patterns (DAMPs), priming plant innate immunity through ancient receptors and defense pathways that most probably evolved to react on microbial fructans acting as microbe-associated molecular patterns (MAMPs). The proposed model is placed in an evolutionary perspective. How this type of DAMP signaling may contribute to cross-tolerance and multistress resistance effects in plants is discussed. Besides apoplastic ATP, NAD and fructans, apoplastic polyamines, secondary metabolites, and melatonin may be considered potential players in DAMP-mediated stress signaling. It is proposed that mixtures of DAMP priming formulations hold great promise as natural and sustainable alternatives for toxic agrochemicals.